2022
DOI: 10.1186/s12884-022-04517-1
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean delivery in Iran: a population-based analysis using the Robson classification system

Abstract: Background The rise of Cesarean Sections (CS) is a global concern. In Iran, the rate of CS increased from 40.7% in 2005 to 53% in 2014. This figure is even higher in the private sector. Objective To analyze the CS rates in the last 2 years using the Robson Classification System in Iran. Methods A retrospective analysis of all in-hospital electronically recorded deliveries in Iran was conducted using th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…It records all birth-related data electronically (demographics, maternal characteristics, medical history, obstetric interventions, pregnancy complications, and perinatal outcomes) across the country since 2013. The national accreditation program confirmed that there is acceptable validity and reliability in the recent years with more than 95% of the registration rate [5]. Almost from the beginning of online birth registry in Iran (2013), surveillance of birth defects has been started.…”
Section: Methodsmentioning
confidence: 95%
“…It records all birth-related data electronically (demographics, maternal characteristics, medical history, obstetric interventions, pregnancy complications, and perinatal outcomes) across the country since 2013. The national accreditation program confirmed that there is acceptable validity and reliability in the recent years with more than 95% of the registration rate [5]. Almost from the beginning of online birth registry in Iran (2013), surveillance of birth defects has been started.…”
Section: Methodsmentioning
confidence: 95%
“…According to the WHO report, the CS rate should not exceed 15% of all deliveries 8 . However, research has reported a higher CS incidence in Iran 9 . Despite the declining trend in MMR in Iran from 1990 to 2013, CS outcomes still account for most maternal mortality in the country 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, all mothers (100%) experienced at least one disrespectful behavior [22]. Moreover, a study by Shirzad et al (2019) showed that mistreatment during maternity care in hospitals was the main reason for choosing cesarean section (CS) by Iranian women, in a context where more than 50% of births take place by CS [24]. Given this context, immediate attention and action is essential to reduce mistreatment and promote RMC in Iran, as one of the most important public health issues.…”
Section: Introductionmentioning
confidence: 99%